Effect of Work Overload and Role Ambiguity on Individual Work Performance of Employees at PT XYZ Unit XYZ Academy - Denik Putri Perdani; Nuri Herachwati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to explore the effect of Work Overload and Role Ambiguity on Individual Work Performance in an organization or unit engaged in education & training and is currently transforming to expand its business processes by serving internal and external customers, with limited organizational capacity and capability XYZ Academy which is currently owned as a Corporate University. Design/methodology/approach – The population of this research is 47 XYZ Academy staff who work in 4 Sections and 6 Campuses spread across the island of Java. Questionnaires were distributed to 47 participants. However, only 43 questionnaires were accepted for further investigation, and these questionnaires were analyzed using SPSS version 22. Several statistical data analysis techniques were used, including descriptive analysis, Statistical Classical Testing, Pearson Correlation, Cronbach's Alpha, Simultaneous F Test, Partial t-Test, and Multiple Regression.Findings – Work overload is not always a predictor of decreased individual employee performance. This increase in workload can be a challenge for employees to be more enthusiastic in improving their performance. However, role ambiguity here is proven to have a significant negative effect on employee performance. Based on research studies at the XYZ Academy Unit with areas of work in education and training as well as the transformation from an internal customer training management unit to a profit-oriented institution, it appears that the additional workload does not have a significant effect on employee performance.Practical implications – This study recommends that XYZ Academy focus more on Role Ambiguity and individual performance practices. Originality/value – This study provides a framework and understanding of Work Overload and Role Ambiguity in Individual Work Performance related to the organization in one model.